TALEN-mediated enhancer knockout influences TNFAIP3 gene expression and mimics a molecular phenotype associated with systemic lupus erythematosus - Wang, Shaofeng (Genes Immun, 2016)
Linkage disequilibrium poses a major challenge to the functional characterization of specific disease-associated susceptibility variants. Precision genome editing technologies have provided new opportunities to address this challenge. As proof-of-concept, we employed TALEN-mediated genome editing to specifically disrupt the TT>A enhancer region to mimic candidate causal variants identified in the systemic lupus erythematosus-associated susceptibility gene, TNFAIP3, in an isogenic HEK293T cell line devoid of other linkage disequilibrium-associated variants. Targeted disruption of the TT>A enhancer impaired its interaction with the TNFAIP3 promoter by long-range DNA looping, thereby reducing TNFAIP3 gene expression. Loss of TNFAIP3 mRNA and its encoded protein, A20, impaired TNFα-induced receptor-mediated downregulation of NF-κB signaling; a hallmark of autoimmunity. Results demonstrate that the TT>A enhancer variants contribute to causality and function independently of other variants to disrupt TNFAIP3 expression. Further, we believe this approach can be implemented to independently examine other candidate casual variants in the future.